Educational Potential of Museums - Burceva, Rita (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
A dual situation comes into existence, where, on the one hand, the role of preservation of the cultural heritage and making it available to public is regularly emphasized in the papers of researchers of education and personal development of people, but, on the other hand, the museum resources and possibilities in life-long learning and self-directed personal development are not sufficiently used in practice. The purpose of the article is to promote the educational significance of the museum environment within the context of the life- long learning dimension. Based on the theoretical analysis of literature and the data obtained through empirical observations, there is a discussion model developed and presented which demonstrates the impact of various internal and external conditions and their relation to the educational potential of a museum in the development and socialization of a man’s personality. There are some isolated cases established in the course of empirical observations when the information received in a museum discords with some bits of previous information visitors have, and these circumstances do not provoke positive emotions.